Partial molar volumes of components of water – aliphatic alcohol mixtures - B. K. Karabekova; A. R. Bazaev (Тонкие химические технологии, 2013)
In this work we used results of p,Vm,T,x-measurements of water – alcohol mixtures (methanol, ethanol and 1-propanol) with x = 0.2, 0.5, 0.8 in the range of temperatures 613.15–653.15 К and pressures 20–50 MPa for calculation of partial molar volumes. The dependence of molar volume on concentration Vm = f(p,x)T is described by a polynomial equation with relative deviation 0.5%. A characteristic feature for all of three studied mixtures is that an insignificant growth of the partial molar volumes of water and a decrease of the partial molar volumes of the alcohols take place with increasing alcohol concentration. Water – hydrocarbon mixtures in the critical state have a similar character of the dependence of partial molar volume on concentration.